Perceptions of cultural landscapes: Exploring tourist satisfaction in traditional villages - Huaheng Shen; Xueqin Tan; Xinmei Liu; Xiting Yu; Yu Luo (AIMS Geosciences)
The cultural landscape of traditional villages is a valuable cultural heritage. Using the example of the Huangdu Dong Village, this study collected data on the perceptions of 209 tourists regarding the cultural landscape of traditional villages using a questionnaire survey. The perceptions and satisfaction rates of tourists were analyzed, and key factors influencing their satisfaction with the cultural landscape were identified. The results show that tourists generally hold a positive perception of traditional village cultural landscapes, with the highest levels of perceptions belonging to folk activity cultural landscapes and clothing cultural landscapes. Additionally, this study identified four key factors that have a significant positive impact on tourist satisfaction with the cultural landscape, namely architectural, water, vegetation, and service facility cultural landscapes. The research also found that tourists residing in rural areas reported significantly higher satisfaction with the cultural landscape than those living in urban areas; moreover, tourists with an income above 10,000 yuan exhibited significantly higher satisfaction compared to other income groups. Finally, based on its findings, this study provides recommendations for optimizing the protection, planning, and design of traditional village cultural landscapes to enhance overall tourist satisfaction.